2010
DOI: 10.1111/j.1752-7325.2009.00145.x
|View full text |Cite
|
Sign up to set email alerts
|

Dental care utilization and retirement

Abstract: Objective: The authors examine the relationship of dental care coverage, retirement, and utilization in an aging population using data from the Health and Retirement Study (HRS). Methods:The authors estimate dental care use as a function of dental care coverage status, retirement, and individual and household characteristics. They also estimate a multivariate model controlling for potentially confounding variables. Results: The authors show that that the loss of income and dental coverage associated with retir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
29
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 6 publications
6
29
0
Order By: Relevance
“…The analysis conducted in this paper clearly demonstrates unequal utilisation of dental care across income groups of the elderly population: the low-income elderly group appears to be less likely to use dental care services compared with their wealthier counterparts (as reflected by the income gradient in the respective odds ratios of consulting a dentist). Generally, such finding is in line with those previously reported in several studies conducted in developed countries [1,2,4,7,10,[18][19][20]. However, by carefully considering the intricate relationship between individuals' incomes and the density of dental practitioners, results indicate that the higher the density of dental practitioners is the lower the role of income would be.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The analysis conducted in this paper clearly demonstrates unequal utilisation of dental care across income groups of the elderly population: the low-income elderly group appears to be less likely to use dental care services compared with their wealthier counterparts (as reflected by the income gradient in the respective odds ratios of consulting a dentist). Generally, such finding is in line with those previously reported in several studies conducted in developed countries [1,2,4,7,10,[18][19][20]. However, by carefully considering the intricate relationship between individuals' incomes and the density of dental practitioners, results indicate that the higher the density of dental practitioners is the lower the role of income would be.…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, the elderly may face significant hurdles before obtaining the necessary dental care [3]. Indeed, previous studies conducted elsewhere have already demonstrated that not only the physically impaired, but also the economically and socially disadvantaged elderly, are more likely to experience tooth loss and edentulism, untreated dental decay and periodontal diseases [4][5][6][7][8][9][10]. Inequalities in access to medical or dental care by income have already been demonstrated [11,12].…”
Section: Introductionmentioning
confidence: 96%
“…However, the oral health behavior of the pensioners was significantly influenced by retirement grade level, indicating that pensioners on grade level 7-17 are more likely to behavior good oral health behavior than those on level 1-6. This is in agreement with other studies which reported that utilization of dental services was found to be more dependent on ability to pay [7,8] and reduced income was accompanied by lower utilization of dental services [10].…”
Section: Discussionsupporting
confidence: 83%
“…Furthermore, Individuals with tertiary education utilise dental service more frequently than those with secondary education and those with secondary education than those with primary education [6][7][8]. Factors such as income and presence of dental insurance are also associated with the number of dental visits among older Americans aged 55-75 years [9] In another study, it was reported that retirement which is usually accompanied by reduced income and dental insurance coverage in developed countries was accompanied by lower Health Knowledge, Attitude and Behavior of Pensioners in Port Harcourt, Rivers State utilization of dental services [10]. Again, observed relationship between SES and oral hygiene has been reported.…”
Section: Introductionmentioning
confidence: 99%
“…There was an association between not using dental services during the past year and a higher probability of being frail and (OR = 2.1, 95% CI 1.2–3.8); Overall, the utilization of dental services among the elderly is lower [43] (49% in this study) than the utilization of medical services (85%) [44]. According to Kiyak [45], elderly people who believe that declining health is a part of aging and that recovery is not possible, reflect that attitude by not utilizing dental services.…”
Section: Discussionmentioning
confidence: 99%